The Online Student Portfolio Implementation at the Faculty of Civil Engineering, Universiti Teknologi MARA, Pulau Pinang Malaysia / Ruqayyah Ismail ... [et.al.] - Ismail, Ruqayyah; Petrus, Clotilda; Marajan, Caroline; Baharom, Bahardin; Ahmad Zakwan, Fariz Aswan (Universiti Teknologi MARA Cawangan Sarawak, 2022)
A student learning portfolio is a documentation of student work that exhibits a student's effort, learning progress, achievements, and competencies gained during a course or time in university. However, compiling a hardcopy student learning portfolio requires excessive physical resources and space. Therefore, an innovative, creative and economical solution is needed for quality student service. Hence the Faculty of Civil Engineering, Universiti Teknologi MARA, Pulau Pinang, has developed an initiative to implement an online student learning portfolio using the Google Sites online platform. This paper has two main objectives. Firstly, to describe the documentation processes of the online student portfolio implementation, which comprises the students' learning reflection, the cumulative Program Outcomes, (PO) attainment, and the progressive learning performance. Secondly, to evaluate the effectiveness of the implementation of the student learning portfolio using an online platform. 863 students participated and successfully produced the online learning portfolio.